“SAYA TIDAK TAKUT MATI” Mispersepsi Terhadap Iklan Bahaya Merokok di Ponorogo - Cholik Harun Rosjidi; Laily Isro’in; Nurul Sriwahyuni (Universitas Muhammadiyah Ponorogo, 2017)
Cigarette consumption in adolescence is very high and there is a tendency to increase every year. Various programs to reduce the consumption of smoke already done one of them is included advertising the dangers of smoking on cigarette packs. Higher cigarette consumption is in line with the increasing number of cardiovascular diseases The threat of cardiovascular disease was not followed by an increase in public awareness. Public misperceptions about the risk factors of cardiovascular disease is still high. This study aimed to analyze the perception of cigarette advertising, value and awareness of adolescents about the dangers of cardiovascular disease in Jenangan Siman Ponorogo. This type of research with a qualitative approach. Subjects were adolescence in the village Jenangan. Determining Subject purposively. Number of subjects in this study 4 participants. Data was collected by in-depth interview techniques. The results of the study as follows: all participants know the dangers of tobacco consumption such as heart disease, impotence and cancer, the majority of smoke when entered junior high school. Smoking is a major factor causing environmental factors. Subjects teen gave a mixed response to advertisements on cigarette packets, most do not inspire fear. Misperception adolescent to advertisements on cigarette packets will affect the pattern of cigarette consumption and the prevention and treatment of cardiovascular disease. Redesign of advertising on cigarette packets should be carried out and based on research.